THE EFFECTIVENESS OF UNPLUGGED ACTIVITIES ON TEACHING VOCABULARY FOR YOUNG LEARNERS AT MI MANSYAUL HUDA - Chyntia Heru Woro Prastiwi; Meiga Ratih Tirtanawati; Inawati, Lisa (Aisyah Journal of English Language Teaching (AIJELT), 2024)
Vocabulary is the basic part and a key element to learning any language. Courage to speak must be supported by adequate vocabulary. If we dare to speak but are not supported by vocabulary, then we may use sign language to express something.. However, to improve memorize of vocabulary, teachers must use a technique or strategy that is suitable, one of which is the use unplugged activity coding game. This research aimed to describe the effectiveness of unplugged activities in teaching vocabulary which is conducted at MI Mansyaul Huda. To explain the effectiveness of teaching vocabulary to young learners, the researcher employed a pre-experimental research approach to get more information in detail. The data were collected through the pre-test and post-test. The population of this research was the 2nd-grade students of MI Mansyaul Huda in the academic year 2023/2024 which consisted of 20 students. The result showed that the use of unplugged activities was effective in teaching vocabulary to young learners evidenced by the increase in pre-test to post-test score. Kosakata adalah bagian dasar dan elemen kunci untuk mempelajari bahasa apa pun. Keberanian berbicara harus ditunjang dengan kosakata yang memadai. Namun untuk meningkatkan hafalan kosa kata, guru harus menggunakan teknik atau strategi yang sesuai, salah satunya adalah penggunaan unplugged aktivitas coding game. Penelitian ini bertujuan untuk mendeskripsikan efektivitas aktivitas unplugged dalam pengajaran kosakata yang dilakukan di MI Mansyaul Huda. Untuk menjelaskan efektivitas pengajaran kosakata bagi pelajar muda, peneliti menggunakan pendekatan penelitian pra-eksperimen untuk mendapatkan informasi lebih rinci. Pengumpulan data dilakukan melalui pre test dan post test. Populasi penelitian ini adalah siswa kelas 2 MI Mansyaul Huda tahun ajaran 2023/2024 yang berjumlah 20 siswa. Hasilnya menunjukkan bahwa penggunaan aktivitas unplugged efektif dalam pengajaran kosakata bagi pelajar muda yang dibuktikan dengan peningkatan nilai pre test ke post test.